Phase transition of p-adic Ising λ-model - Dogan, Mutlay; Akin, Hasan; Mukhamedov, Farrukh (American Institute of Physics, 2015)
We consider an interaction of the nearest-neighbors and next nearest-neighbors for the mixed type p-adic λ-model with spin values {−1, +1} on a Cayley tree of order two. In the previous work we have proved the existence of the p-adic Gibbs measure for the model. In this work we have proved the existence of the phase transition occurs for the model.